Acquired Brain Injuries and Intimate Partner Violence: A Situational Analysis of Help Seeking Barriers in Rural Northern New England - Amanda St Ivany; Donna L. Schminkey; Michelle L. Munro-Kramer (SAGE Publishing, 2021)
Nurses care for women experiencing non-fatal strangulation and acquired brain injuries whether or not it is disclosed. Situational analysis was used to analyze 23 interviews from Northern New England with survivors, healthcare workers, and violence/legal advocates to explore overlapping relationships between violence, acquired brain injuries, non-fatal strangulation, and seeking care. Findings included the concepts of paying social consequences and the normalization of violence. Non-fatal strangulation was described as increasingly related to violence and other areas. Repetitive acquired brain injuries can impair functioning needed to address violence and healthcare providers and advocates are generally unaware of the impact of acquired brain injuries. A lack of resources, training, and tools for acquired brain injury screening were barriers in recognizing and responding to it, causing hidden symptoms. This study adds to the literature examining intimate partner violence in rural areas; specifically intimate partner violence-related acquired brain injuries in rural areas.